Ileocolic Anastomoses - Gleason, Lauren; Gunnells, Drew, Jr (Clinics in Colon and Rectal Surgery, 2022)
Ileocolic anastomoses are commonly performed by surgeons in both open and minimally invasive settings and can be created by using many different techniques and configurations. Here the authors review both current literature and the author's preference for creation of ileocolic anastomoses in the setting of malignancy, inflammatory bowel disease, and colonic inertia. The authors also review evidence surrounding adjuncts to creation of anastomoses such as use of indocyanine green and closing mesenteric defects. While many techniques of anastomotic creation have adapted with new evidence and technologies, several key principles still provide the foundation for current practice.
Keywords: ileocolic; anastomosis; colectomy